Symptomatic cavernous hemangioma of fronto-parietal region of the brain in a young female patient – a case report - Kulczyński, Marcin; Chudzik, Robert; Tomaszewski, Mateusz; Marciniec, Michał; Papuć, Ewa; Rejdak, Konrad (Journal of Education, Health and Sport, 2018)
Introduction: Cavernous hemangioma is a bening blood vessel malformation that can be located in the central nervous system. Although most patients who are found to have a CNS hemangioma are asymptomatic, the entity can cause a wide spectrum of symptoms including severe ones like epileptic seizures, stroke, diplopia, dysfasia or cognitive functions’ disorders.Case report: A 21-year-old female patient was admitted to the Department Of Neurology due to transient vision impairment, dysfasia, headache and tinnitus. Physical examination revealed no focal neurological signs. A brain MRI was performed. A cavernous hemangioma of 7-8 mm in size was found. The patient was examined by neurosurgeon as well, who did not qualify her for an immediate surgery.Discussion: Although cavernous hemangiomas are often asymptomatic, sometimes they can be a causative factor of different neurological symptoms. One should always take into account a possibility of cerebral hemangioma presence in young patients that suffer from headaches, tinnitis or have impaired vision.